Nasir al-Din al-Tusi's understanding of trigonometry - Isqeel , Abdullateef Ayodele; Faris, Waleed Fekry (IIUM Press, 2011)
The methodology adopted in this chapter is library and internet based. The data used were collected from dependable sources. The objective of this chapter is to investigate the understanding of Nasir aI-Din al-Tusi's work in trigonometry and to derive and analyze the scope of sine law which initiated by al - Tusi. The significance of this chapter is the usefulness of the sine law to various fields such as astronomy, geography and medicine. Trigonometry is a branch of mathematics concerned with specific functions of angles and their application to calculations. It is derived from two Greek words trigon meaning "triangle" and metron meaning "a measurement". Hence, it is a methodology for finding some unknown elements of triangle provided the data include a sufficient amount of linear and angular measurements to define a shape